Comparative utilization of urea and fungal treated mustard straw by sheep - MISHRA, A S; CHATURVEDI, O H; MISRA, A K; KARIM, S A (The Indian Journal of Animal Sciences, 2014)
The present study was conducted to detennine relative efficacy of urea and fungal treated mustard straw in maintaining adult sheep. Mustard straw (MS) treated with urea (UTMS) and fungus (FTMS) was fed ad lib. to ewes in G1 and (i) respectively, along with 200 g concentrate mixture/head/day. Urea treatment ofMS increased its CP content from 3.7 to 7.2% which further increased to 7.7% in FTMS. Hemicellulose and cellulose content decreased with proportionate increase in NDF and ADF in UTMS while the cell wall constituents further decreased in FTMS. Daily DMI in unit body weight or metabolic body size was higher (P<0.01) in FTMS fed animals. Digestibility of DM, NDF and ADF increased (P<0.01) and hemicellulose decreased (P<0.01) in OG2 compared to G1 Although nutritive value of the lest diets was similar, DE intake in metabolic body size was higher in G2 Both G1 and G2 were in positive N balance, however, per cent N retention was comparatively lower (13.2%). Feeding ofUTMS or FTMS along with 200 g concentrate maintained sheep, whereas treatment of MS with Coprinus fimetarius did not add advantage over the urea treated MS.